Peran Virtual Experiential Marketing dan Brand Trust terhadap Brand Loyalty: Peran Virtual Experiential Marketing dan Brand Trust terhadap Brand Loyalty - khoirunissa, Alvi diani; Rufaidah, Popy (Fakultas Seni Rupa dan Desain ITB, 2024)
The purpose of this study is to analyze the role of virtual experiential marketing and brand trust in brand loyalty among virtual try-on cosmetic filter users in Indonesia. An online tool made using Google Forms and shared on social media was used to perform the research. SEM-PLS was the statistical method employed to examine 287 convenience sample data. The results showed that virtual experiential marketing has a positive impact on brand loyalty, and brand trust has a positive impact on brand loyalty. The study recommends the most effective indicators of virtual experiential marketing, identifying external factors that influence a cosmetics brand's strategy in Indonesia in forming trust and loyalty, and using the virtual try-on filter feature to build trust through positive virtual experiences.